Taxation, Innovation, and Entrepreneurship - Hans Gersbach; Ulrich Schetter; Maik T. Schneider (ETH Zurich, CER-ETH - Center of Economic Research, 2014)
We explore optimal and politically feasible growth policies in the form of basic research investments and taxation. Basic research is a public good that benefits innovating entrepreneurs, but its provision and financing also affect the entire economy – in particular, occupational choices of potential entrepreneurs, wages, dividends, and aggregate output. We show that the impact of basic research on the general economy rationalizes a taxation pecking order to finance basic research. More specifically, in a society with desirably dense entrepreneurial activity, a large share of funds for basic research should be financed by labor taxation, while a minor share should be left to profit taxation. Such tax schemes will induce a significant proportion of agents to become entrepreneurs, thereby rationalizing substantial investments in basic research that fosters their innovation prospects. These entrepreneurial economies, however, may make a majority of workers worse off, giving rise to a conflict between efficiency and equality. We discuss ways of mitigating this conflict and thus strengthening the political support for growth policies.
Keywords: D72; H20; H40; O31; O38; 330; Basic research; economic growth; entrepreneurship; income taxation; political economys